Receptor expression for IgG constant fraction in human umbilical vein endothelial cells. - Alberto, Maria Fabiana (2000)
Endothelial cells (EC) lining the vasculatureform a natural barrier between the circu- immune complex levels, whereby patients with thelating blood and the underlying tissue. One highest disease scores tend to have the highest levelof the major functions of these cells is to prevent of immunocomplexes (IC) [4]. Moreover, patientsplatelet deposition and activation of the coagula- with active SLE contain IC that bind to EC oftion cascade [1].